Effect of NPK fertilizer and root fertilizers Inicium on some physiological characters of Lycopersicon esculentum and its effect on mitotic division index of seedling radical apex (Baghdad Science Journal, 2014)
The experiment was carried out to study the effect of NPK and Inicium using two concentration for each of them 1 and 2 gm/L for NPK and 5 and 10 ml/L for Inicium on some physiological characters of Lycopersicon esculentum and mitotic division index of seedling radical apex. The results showed that all the characters increased plant height, stem diameter, leaves number, length of leaf, lobs number in one leaf, length of root and root diameter. The data showed that the percentage of cell division, mitotic division and Telophase stage increased in seedling radical apex comparison with control plants.